DIPG-37. DEVELOPMENT AND CHARACTERIZATION OF DIFFUSE INTRINSIC PONTINE GLIOMA MOUSE MODELS GENERATED BY BRAINSTEM IN UTERO ELECTROPORATION. Issue 2 (22nd June 2018) - Patel, Smruti; Hartley, Rachel; Bear, Heather; Phoenix, Timothy
Abstract: Diffuse intrinsic pontine glioma (DIPG) is a universally fatal pediatric cancer arising in the brainstem of children. Their unique brainstem location and pathology, including limited disruption of the blood-brain barrier (BBB), present a significant challenge to treatment. Developing mouse models that accurately reflect the genetic landscape and brainstem location of DIPG will be critical to delineate the role of newly identified mutations in DIPG pathogenesis. Here we describe the efficient generation of DIPG mouse models by targeted transfection of the developing brainstem using in utero electroporation, and characterize the pathological and molecular features associated with PDGFB, Pdgfra, and H3.3 K27M genetic variants. Both PDGFB and Pdgfra D842V expression, in combination dominant negative Trp53 (DNp53), develop fully penetrate high-grade gliomas that display distinct differences in latency, histology, and molecular profiles. Addition of the H3.3 K27M mutation alters gene expression in both PDGFB and Pdgfra D842V tumors, but only significantly accelerated Pdgfra D842V tumors in this system, likely due to the already aggressive nature of PDGFB tumors. Compared to PDGFB tumors, Pdgfra D842V brainstem tumors maintain BBB function. Paracrine effects of PDGFB expression in the tumor microenvironment are associated with disruption of pericyte-endothelial interactions, extracellular matrix remodeling, and increased angiogenesis and BBB disruption. This DIPG mouse modeling system provides a rapid and flexible in vivo platform to perform functional genomic studies to fundamentally advance our understanding of the cellular and molecular basis underlying DIPG, and conduct preclinical studies of molecularly targeted therapies that aim to improve survival rates and outlook for DIPG patients and their families.